MACEDONIAN LANGUAGE AND ITS AUSBAU AND ABSTAND DIMENSION APPLIED TO CONSTITUTIONAL LAW (Journal of Contemporary Philology, 2024)
The article discusses the concepts of Ausbau and Abstand languages and their application to the Macedonian language. It outlines the instances when Macedonian can be seen as Ausbau or Abstand language. At the same time, it also deals with the level of law, specifically with the branch of constitutional law, and shows that the five main reasons for enshrining the language in the Constitution of North Macedonia (national identity, dominance of language, protection of language, consolidation of sovereignty and consolidation of the language in international relations, and foreign policy) correlate precisely with these sociolinguistic concepts. It therefore concludes that it is possible to link certain reasons for enshrining a language as a norm of constitutional law to whether Macedonian is viewed as an Ausbau or Abstand language. The paper contains a classification of these reasons for constitutional regulation based on these two concepts.
Keywords: Macedonian language; Ausbau/Abstand languages; applied sociolinguistics; law; constitution